The evolution of the cytokine profile under the influence of immunomodulator glutamine-cystine-glycine disodium in patients with destructive multidrug-resistant lung tuberculosis - E. N. Raznatovskaya (Zaporožskij Medicinskij Žurnal)
Importance of the problem caused by the necessity of treatment efficiency improving in patients with multidrug-resistant destructive pulmonary tuberculosis (MDR).